2015
DOI: 10.1016/j.jma.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical and mechanical properties of AZ91D/SiC composites by two step stir casting process

Abstract: Magnesium alloy (AZ91D) composites reinforced with silicon carbide particle with different volume percentage were fabricated by two step stir casting process. The effect of changes in particle size and volume fraction of SiC particles on physical and mechanical properties of composites were evaluated under as cast and heat treated (T6) conditions. The experimental results were compared with the standard theoretical models. The results reveal that the mechanical properties of composites increased with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…By further increasing the weight fraction of TiB 2 to 15%, the hardness value reaches a maximum of 58.56 HV. The interface between the matrix and the reinforcement phase plays a major role in enhancing their mechanical and tribological properties [31,32]. In the present study, the interface between the Mg-Cu matrix and the reinforcement is good, as shown in Figs.…”
Section: Microstructure Analysis Of Mg-cu Alloy-tib 2 Compositessupporting
confidence: 58%
See 1 more Smart Citation
“…By further increasing the weight fraction of TiB 2 to 15%, the hardness value reaches a maximum of 58.56 HV. The interface between the matrix and the reinforcement phase plays a major role in enhancing their mechanical and tribological properties [31,32]. In the present study, the interface between the Mg-Cu matrix and the reinforcement is good, as shown in Figs.…”
Section: Microstructure Analysis Of Mg-cu Alloy-tib 2 Compositessupporting
confidence: 58%
“…But, the compressive strength of the composite gradually increases with the increase in weight percentage of TiB 2 . It is well known that the strengthening effect of the composite depends on (a) load-bearing effects, due to the presence of reinforcements, and (b) Hall-Petch effect, due to the grain size refinement and the generation of geometrically necessary dislocations to accommodate thermal and elastic modulus mismatch between the matrix and reinforcements [31]. The reason for increasing compressive strength is that the work hardening occurs, when the composite is strained.…”
Section: Mechanical Properties Of Mg-cu Alloy-tib 2 Compositesmentioning
confidence: 99%
“…The proper milling parameters make the TiO 2 particles to disperse uniformly in the magnesium matrix. However the different density of matrix and reinforcement particles leads to increased porosity with the increase in weight percentage of reinforcement [17]. The size of the TiO 2 particle is less than the matrix particle size.…”
Section: Effect Of Tio 2 On the Density And Porosity Of Mg Matrix Commentioning
confidence: 99%
“…The slurry can be ensured molten throughout the pouring by this process. Die is preheated in order to attain uniform solidification [18]. If the die is not preheated uneven solidification takes place and crystalline structure and boundary formed will not be as desired.…”
Section: Preparatory Functionsmentioning
confidence: 99%